Identifying the Practical Application of Computational Fluid Dynamics Techniques - Annapurna Ramakrishna Shinde, Nilesh Parmar (Mathematical Statistician and Engineering Applications, 2022)
For issues involving one or more of the following phenomena fluid flow, heat transfer, mass transfer, and chemical reaction computational fluid dynamics (CFD) is a well-established instrument of choice. This article provides a concise summary of the many ways fluid mechanics may be put to use in everyday life, including in the fields of aviation, engineering, shipbuilding, and more. It lays out the path for the future of computational fluid mechanics research and identifies the problems and gaps in the current state of the field. It is argued that CFD offers many prospects for the study of industrial activity, and that these prospects will grow in importance and breadth as computer technology and software continue to improve.